Certain predictors of coping with stress in adolescents - Elżbieta Napora; Vlasta Cabanová; Marta Kolařikova (Health Psychology Report, 2022)
Background The purpose of the study was to search for variables that show a relationship with coping with stress as well as to search for the possibility of predicting a stress coping mechanism in the studied adolescents. Two questions were formulated in the study: Are mental resilience and communication with peers significant predictors of coping with stress in the studied group? To what extent will the analysed predictors explain individual strategies to cope with stress?